The influence of preparation technology on phase transitions in NaNO2 embedded into porous glass - Rysiakiewicz-Pasek, Ewa; Jaguś, Paweł (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
The dielectric properties of sodium nitrite embedded into porous glasses with the average pore diameter of 45 nm and 320 nm have been studied. The samples were obtained by immersion of empty porous glass into the melted NaNO2 and then they stayed there for 24 and 8 hours. The sequence of phase transitions (PT) from the paraelectric phase to the sinusoidal antiferroelectric phase and to the ferroelectric phase has been observed in these nanocomposite materials on cooling. It is shown that due to the size effect, the temperatures of these PTs are lower than in bulk NaNO2.
Optica Applicata, Vol. 38, 2008, nr 1, s. 101-107
Keywords: optyka; porous glass; ferroelectric; phase transition; size effect